The language of time a reader - Mani, Inderjeet; Pustejovsky, J. (James); Gaizauskas, Robert (New York : Oxford University Press, 2005)
"This book includes selected classic and contemporary papers in four areas: tense, aspect and event structure; temporal reasoning; the temporal structure of natural language discourse; and temporal annotation. Introductions to each area provide technical background for the non-specialist, explaining the underlying connections across disciplines"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Grammar, Comparative and general -- Temporal constructions; Space and time in language; Electronic books